(3OjhGf GHf GdhQOjs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3hChd TYQ GdOjhGf bhdg(B: (3CrOQ CMGOjK SdY hGdMei COQ hGdgrL HPcQ Gdpqdhi Ch HGfg GdYWQ s
(3BNQgG (B:s
(3hBNQ TYQ GdOjhGf bhdg(B: (3CfTQ JCgjdc Hj CYXeG aMb dj hGddg Cf CYXeG Ke jdjg GdefKhQhBNQ GdeZahQ bhdg(B: (3hGdQCj GdYGdj aj Pdc CYdi s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B250 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI djOf (B(861) s
Keywords: (3GdCOHs